PENGARUH EKSTRAK BROTOWALI (Tinospora crispa L.) TERHADAP SIKLUS REPRODUKSI MENCIT (Mus musculus L. Swiss Webster) - Rahim, Aulia - (Pendidikan Biologi, 2014)
Brotowali (Tinospora crispa L.) have containt of alkaloid and it used as natural contraception. Contraception like pill, insection and IUD which distributed by government also has negative impact, because of that we need to find the alternative from plants which has potential to be a contraception. The aim of this researh is to find out the effect of brotowali extract toward the cycle reproduction of mice (Mus musculus L. Swiss Webster). This research used completely randomized design with 4 treatment and 6 replycation. The object which use in this test is female mice with weight 20-25 gram. Giving extract via oral used gevage needle with 0,5 cc volume for 26 days. The result showed brotowali extract can extenting of estrus cycle. Extenting estrus cycle reach out until Â±13day (in one estrus cycle), extending proestrus and metestrus phase, where cutback in estrus phase. The largest added time in proestrus phase was found in B (1, 35 days) and D (1,93 days) in metestrus phase, whereas not significantly P < 0,05 in diestrus phase. Then in the control of estrus phase founded (1,4 days) and cutback in D (0,5 days), and in one estrus cycle we get total time on control (5,67 days), B (10,5 days), C (11,33 days) and D (12,80 days). It can conclude that the extract of brotowali directly influence reproductive cycle of the mice by axis hipotalamus, hipofisis and ovarium mechanism.